Assistance in Underage Abuse Case at Klaten Police - Marisa Kurnianingsih; Muthia Aulia Alyda; Haekal Septiawan; Andria Luhur Prakoso; Arief Budiono; Achmadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The abuse of minors is a serious crime that violates children's rights and has long-term impacts on the physical, emotional, and psychological well-being of victims. Legal protection for children who are victims of abuse requires an approach that focuses on protecting children and their recovery. This study aims to explore the practice of accompanying cases of sexual abuse of minors at the Klaten Police Department and to analyze the effectiveness of assistance in the criminal justice system. The research method used is an advocacy method with a focus on legal assistance. Assistance is carried out during the examination process, from consultation to assistance in making reports to the police. This research is expected to contribute to the development of policies and practices for better assistance in cases of sexual abuse of minors.